Description of Ventricular Arrhythmia after Taking Herbal Medicines in Middle-Aged Couples. (1st October 2020) - Zakeri, Mohammad Ali; Mohammadi, Vahid; Bazmandegan, Gholamreza; Zakeri, Maryam
Abstract : Medicinal herbs and some derivatives have been used in the treatment of heart disease which is rarely responsible for ventricular arrhythmias and cardiac arrest. Ventricular tachycardia (VT) increases the risk of sudden cardiac death (SCD). However, only a few reports are available about the cardiac ventricular arrhythmia followed by taking herbal medicines. We present two patients (a couple) without a history of heart disease who referred to the hospital with ventricular arrhythmia.